Web Services and Formal Methods 9th International Workshop, WS-FM 2012, Tallinn, Estonia, September 6-7, 2012, Revised Selected Papers - Beek, Maurice H. ter.; Lohmann, Niels; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the 9th International Workshop on Web Services and Formal Methods, WS-FM 2012, held in Tallinn, Estonia, in September 2012. The 9 papers presented were carefully reviewed and selected from 19 submissions. They cover aspects such as the modeling and analysis of web services, service discovery, and service coordination with formal methods like BPEL, CSP, Maude, and Petri nets.
Keywords: Computer science; Software engineering; Programming languages (Electronic computers).; Computer logic; User interfaces (Computer systems).; Management information systems; Computer Science; Information Systems Applications (incl. Internet).; Software Engineering; Management of Computing and Information Systems; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; User Interfaces and Human Computer Interaction; Electronic books